Synthesis of hyrostabilizer optimal correction - Кривоносенко, А. П.; Юрченко, А. Н. (Proceedings of National Aviation University (archive), 1999)
Solved is multidimensional problem of the synthesis of optimal stabilization system of hyrostabilizer with the account of the real disturbances acting during flight. The synthesis of optimal structure of the correction system of single axis hyrostabilizer is given as an example to illustrate the efficiency of optimal system relative to the existing one